Sickle cell disease prevention: How prepared are the senior secondary school students in Surulere Local Government Area, Lagos, Nigeria? - Oluchi J. Kanma-Okafor; Adetola O. Abolarinwa; Omobola Y. Ojo; Ekanem E. Ekanem (AOSIS, 2022)
Background: Sickle cell disease (SCD), a common hereditary disease, can be prevented by preparing young people ahead of the conception of an affected foetus. Aim: To assess the knowledge and attitude regarding SCD amongst senior secondary school students in Surulere Local Government Area (LGA), Lagos, Nigeria. Setting: Senior secondary schools in Surulere LGA. Methods: This was a descriptive cross-sectional study amongst 300 senior secondary school students. Data were collected using a self-administered questionnaire and analysed using Stata16. The Chi-square and Fisher's exact tests were used to determine the association between categorical variables. The level of significance was predetermined at p  0.05. Results: The mean age of the respondents was 15.2 (±1.3) years, with a male-to-female ratio of about 1:2. The majority (90.0%) of the respondents were aware of SCD, 63.0% had good knowledge, although less than half of them (46.3%) knew SCD to be a blood disorder, whilst about two-thirds (53.1%) knew that it was an inherited condition. About one fifth (24.4%) of them knew about prevention by genetic counselling. The majority (97.0%) of them had a positive attitude towards SCD. Over two-thirds (72.6%) were aware of their genotype. The prevalence of SCD was 2.0%, whilst 18.9% of them were carriers of the sickle cell trait. Knowing their SCD status but not necessarily their genotype was significantly associated with their attitude towards the disease (p = 0.014). Conclusion: The prevention of SCD was not known to the majority, and better attitudes were more likely when the SCD status was known. Therefore, routine screening and counselling could potentially aid SCD control.